A rare case of secondary small bowel volvulus laparoscopically repositioned: literature review and classification - Koichi Inukai; Hidehiko Kitagami; Shuhei Uehara; Hirotaka Miyai; Nobuhiro Takashima; Minoru Yamamoto; Kenji Kobayashi; Moritsugu Tanaka; Tetsushi Hayakawa (Surgical Case Reports, 2018)
Abstract Background Secondary small bowel volvulus is a rare condition caused by adhesions after laparotomy or tumors. There are no clear guidelines for indication of laparoscopic surgery. Case presentation A 69-year-old male visited our hospital complaining of epigastric pain. He had a history of hypopharyngeal carcinoma treated via pharyngolaryngoesophagectomy with restoration of esophageal continuity by harvesting a free jejunal autograft 6 years ago. Enhanced computed tomography revealed the whirl sign. An emergency laparoscopic operation was performed following a diagnosis of small bowel volvulus. This revealed rotation of the whole small bowel, involving the superior mesenteric artery as the center, and originating at the adhesion of the proximal and distal small bowel. Laparoscopic manipulation of volvulus and lysis of the adhesion were performed. The patient’s postoperative course was uneventful, and he was discharged on hospital day 5. Conclusions Laparoscopic surgery may be useful for treating small bowel volvulus; however, the patient’s treatment indications should be judged carefully.